Nurse managers implementing the lean management system: A qualitative study in Western Canada. (25th February 2020) - Udod, Sonia A.; Duchscher, Judy Boychuk; Goodridge, Donna; Rotter, Thomas; McGrath, Petrina; Hewitt, Anna Dawn
Abstract: Aim: This study explores the perceptions and experiences of nurse managers involved in implementing the Lean management system in a Western Canadian province. Background: The provincial government of Saskatchewan, Canada, implemented a multimillion‐dollar investment in the Lean management system to transform health care delivery by reducing waste and increasing efficiency of processes and outcomes. Methods: This qualitative exploratory study employed semi‐structured interviews with 14 nurse managers in urban and rural health regions in one Canadian province. Results: Six themes outline the difficulties nurse managers experienced in juggling role responsibilities alongside a poorly implemented change system with scarce resources. Conclusion: The results showed tensions in the implementation of a Lean model adapted in the context of health care organisations. The expectations for nurse managers to be pivotal players in the implementation of transformative health care practices that promote and sustain strategies to reduce waste, improve coordination and increase patient safety require investment in leadership development. Implications for Nursing Management: Lean management systems significantly impact the roles of nurse managers who require adequate resources and training to successfully adapt. The results of this study may be used for more effective support mechanisms for nurse managers.